SCIENTIFIC AND THEORETICAL BASIS OF USING INTERACTIVE METHODS IN THE EDUCATIONAL PROCESS - Inobat Ravshanovna Radjabova (International Journal of Innovations in Engineering Research and Technology, 2022)
This article is dedicated to show the theoretical and practical aspects of turning students into subjects of the educational process, i.e. executors, let them solve educational problems independently and add interactive methods to the national education system in the present conditions, where the speed of the flow of information has increased unimaginably due to the era of globalization and scientific-technical progress.